COMBINATION OF FANTASY AND REALISM IN LITERATURE - Shokhsanam Marufova (Western European Studies, 2025)
The combination of fantasy and realism in literature has long been a subject of scholarly discussion, as it allows for an engaging exploration of both the real and the imaginary within a single narrative. This paper examines how authors blend these two elements to create compelling stories that resonate with readers on both a symbolic and literal level. By analyzing various literary works, we identify the key techniques employed to merge fantasy and realism and explore their impact on the reader’s perception of reality and imagination. Additionally, this study highlights the historical evolution of this literary approach and its significance in contemporary literature. The research aims to provide insights into the artistic and philosophical implications of the fusion of fantasy and realism, shedding light on its role in shaping literary narratives across different cultural contexts
Keywords: Fantasy; realism; literary fusion; narrative techniques